Implementasi Kebijakan Pembebasan Biaya Kesehatan Dasar - Akadun, Akadun (FIkom Unisba, 2008)
This study aims to analisys the role organization communication in implementing public policy of free-cost of basic health service. The result indicate that organization communication role for depending in implementing public policy successfull and become trigger other critical factor of implementing policy succesfull, as like resource, bureaucratic structure, and disposition or attitude. Quality of information media, information accessibility, information fidelity, information spreading, information load is urgent to implementing public policy successful.